A taxa ótima de hedge no mercado brasileiro do boi gordo: uma abordagem com BEKK, DCC e BEKK com dummies de safra e entressafra - Lazzarini, Dárcio Aurélio Benetton (2010)
This dissertation has three objectives. The first is to find out the best method to calculate the optimal hedge ratio of the brazilian market of live cattle. In order to do this, five models were tested: BEKK, DCC of Tse and Tsui (2002), DCC of Engle and Sheppard (2001), BEKK with crop dummy and BEKK with intercrop dummy. The second is to calculate the gap between the hedge ratio in the crop and in the intercrop, whereas the hedge ratio in the intercrop must be higher than in the crop because the higher uncertainty about a negative impact on the offer, which would affect negatively the cost of the slaughter houses. The third and last objective is to unveil the fact that the brazilian literature of the optimal hedge ratio is finding very short estimations of this hedge ratio compared with those used on the market. The Conclusion is that the DCC’s models have the best performance by the variance reduction criteria and Sharpe index increase criteria and that the hedge ratio in the intercrop must not be higher than in the crop. Another finding is that the gap of the intertemporal expectation caused by the contractual change implies a higher variance on the future return series, which decrease the hedge ratio.